2015
DOI: 10.1016/j.virol.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 inhibits HBV entry through NTCP down regulation

Abstract: Hepatitis B virus (HBV) infection is a major public health problem. Recently, the human liver bile acid transporter Na(+)/taurocholate cotransporting polypeptide (NTCP) has been identified as an HBV specific receptor. NTCP expression is known to be strongly regulated by IL-6. This study was aimed at characterizing the effect of IL-6 on HBV entry. HBV entry was inhibited by up to 90% when cells were pretreated with IL-6 as shown by a strong inhibition of long term HBsAg secretion. This effect was confirmed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 40 publications
3
72
0
1
Order By: Relevance
“…The findings are not only of interest for the understanding of hepatocellular bile acid handling and TUDC action in liver, but may also be relevant for hepatitis B virus entry into the hepatocyte, which was recently shown to be mediated by NTCP (51). Indeed, recent data suggest that interleukin-6 inhibits hepatitis B virus entry into the hepatocyte through down-regulation of NTCP (52).…”
mentioning
confidence: 81%
“…The findings are not only of interest for the understanding of hepatocellular bile acid handling and TUDC action in liver, but may also be relevant for hepatitis B virus entry into the hepatocyte, which was recently shown to be mediated by NTCP (51). Indeed, recent data suggest that interleukin-6 inhibits hepatitis B virus entry into the hepatocyte through down-regulation of NTCP (52).…”
mentioning
confidence: 81%
“…However, other studies have arrived at contradictory conclusions. One study reported that IL-6 strongly inhibited HBV entry [40], which is inconsistent with previous studies [39]. Sodium taurocholate cotransporting polypeptide (NTCP) is a multiple transmembrane transporter predominantly expressed in the liver [50], and is recognized as an HBV-specific receptor that binds to the N-terminal part of the pre-S1 region of the large envelope protein [51].…”
Section: Il-6-mediated Hbv Entrymentioning
confidence: 80%
“…Conversely, IL-6 can also mediate HBV entry into hepatocytes [39]. However, there are also conflicting reports that IL-6 inhibits HBV entry through the down-regulation of an HBV-specific receptor [40]. IL-6 also induces an inhibitory effect on HBV replication [41].…”
Section: Effects Of Il-6 On Hepatitis B Infectionmentioning
confidence: 99%
“…Conversely, introduction of NTCP cDNA into HepG2 and Huh7 cells conferred susceptibility to infection by HBV and HDV, respectively (16). These seminal findings established NTCP as an HBV and HDV receptor, a demonstration that has been independently confirmed and extended (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Consequently, NTCP substrates or inhibitors such as tauroursodeoxycholic acid (TUDCA), cyclosporine, irbesartan, and ritonavir could suppress ccHBV or HDV infection (18,(20)(21)(22)(23)(24).…”
mentioning
confidence: 89%